Investigation of unsaturated permeability function of soil with multi-modal porosity - Lee, Boris Su Sheng (Nanyang Technological University, 2023)
The fundamental parameters determining most of the engineering features of soil are hydraulic properties, such as the unsaturated permeability function and soil-water characteristic curve (SWCC), which are studied in unsaturated soil mechanics. Soil stability refers to the ability of soil to maintain its structure and resist erosion, compaction, and other forms of degradation. This can be achieved by accurately measuring the soil's soil-water characteristic curve (SWCC) and unsaturated permeability function. Soils with multimodal porosity and characteristics have shown to have greater water retention capabilities which help slope stability against rainfall, plant wilting during the extended drought, and infrastructure damage caused by heaving and subsidence. By adjusting or enhancing the physical and chemical properties we can affect its SWCC, improving the soil's water retention and hydraulic properties to enable soil to withstand heavy precipitation better, maintains moisture during droughts, and provides a more stable foundation for infrastructure, reducing the risks of slope failure, plant wilting, and infrastructure damage. This can lead to improved crop yields, reduced water usage, increased carbon sequestration, and better overall soil health. Additionally, it can help to mitigate the effects of climate change, as the optimized soil can better absorb and retain water, reducing the risk of flooding and improving groundwater recharge. Overall, optimizing the SWCC is an important strategy for improving soil quality and resilience, which can have a wide range of positive impacts on the environment and human society.